Teaching Humanity and Spirituality through Kitab Kuning: An Insight from Pesantren As-Shuffah - Ubaidillah; Kamil, Achmad Muchamad; Diasyhuri, Alfian Mahbub; Khasanah, Salsalatul (Nadwa: Jurnal Pendidikan Islam, 2023)
Most people understand that the learning of Kitab Kuning in pesantren is more focused on the normative teachings of students referred to from at-turast written in Arabic. Therefore, to be able to understand it, it is necessary to have the ability to understand the science of nahwu, sharaf, mufradat, balaghah, mantiq, kalam, fiqh, and Sufism. Apart from the general understanding of learning in Pesantren, it turns out that researchers have found the meaning of humanity and spirituality from the treasures at turast that the students learn. The learning strengthens student s' attitudes toward religious moderation and their attitude to diversity amid the diversity of Indonesian society. The researcher obtained this finding while learning the process in Pesantren As-Shuffah Rembang. This study used the phenomenological and autoethnography methods. From this method, the researcher found the meaning of humanity and spirituality of Kitab Kuning, because it is inseparable from the strengthening of learning in understanding the humanity of the Kitab Kuning language. This learning strengthening is carried out through the following: first, strengthening the existence of Kiai during the study of turast; Second, the presence of Kiai forms students' awareness of their universal intelligence. Third, introducing the instrument validates the meaning of the Kitab Kuning from the perspective of maqashid as shari'ah. Fourth, students' linguistic reasoning is strengthened to understand the humanity of the Kitab Kuning.